Positioning Preterm Newborns for Cardiorespiratory Stability A Global Insight: Memposisikan Bayi Baru Lahir Prematur untuk Stabilitas Kardiovaskuler Sebuah Wawasan Global - Haneen Abdul Hussein Shamkhi; Adraa Hussein Shawq (Universitas Muhammadiyah Sidoarjo, 2024)
This study assessed the effects of supine, prone, and right lateral positioning on the cardiorespiratory indicators of preterm newborns using a randomized controlled trial with 60 participants. Measurements of heart rate, respiratory rate, and oxygen saturation were taken before and after the application of these positions over three days. Results indicated significant improvements in all cardiorespiratory parameters in the intervention groups (p = 0.000), while the control group showed no significant changes. The findings suggest that strategic positioning can be an effective part of developmental care in neonatal intensive care units, enhancing the stabilization of vital functions in preterm newborns. Highlights: Strategic Positioning: Enhances cardiorespiratory stability in preterm newborns. Methodological Rigor: Employs a robust randomized controlled trial. Practical Implications: Recommends routine NICU positioning strategies. Keywords: Preterm Newborns, Cardiorespiratory Stabilization, NICU, Positioning Strategies, Randomized Controlled Trial.